Clinical Selection Strategies to Identify Ischemic Stroke Patients With Large Anterior Vessel Occlusion: Results From SITS-ISTR (Safe Implementation of Thrombolysis in Stroke International Stroke Thrombolysis Registry). Issue 2 (February 2017) - Scheitz, Jan F.; Abdul-Rahim, Azmil H.; MacIsaac, Rachael L.; Cooray, Charith; Sucharew, Heidi; Kleindorfer, Dawn; Khatri, Pooja; Broderick, Joseph P.; Audebert, Heinrich J.; Ahmed, Niaz; Wahlgren, Nils; Endres, Matthias; et al.
Abstract : Background and Purpose—: The National Institutes of Health Stroke Scale (NIHSS) correlates with presence of large anterior vessel occlusion (LAVO). However, the application of the full NIHSS in the prehospital setting to select patients eligible for treatment with thrombectomy is limited. Therefore, we aimed to evaluate the prognostic value of simple clinical selection strategies. Methods—: Data from the Safe Implementation of Thrombolysis in Stroke International Stroke Thrombolysis Registry (January 2012–May 2014) were analyzed retrospectively. Patients with complete breakdown of NIHSS scores and documented vessel status were included. We assessed the association of prehospital stroke scales and NIHSS symptom profiles with LAVO (internal carotid artery, carotid-terminus or M1-segment of the middle cerebral artery). Results—: Among 3505 patients, 23.6% (n=827) had LAVO. Pathological finding on the NIHSS item best gaze was strongly associated with LAVO (adjusted odds ratio 4.5, 95% confidence interval 3.8–5.3). All 3 face–arm–speech–time test (FAST) items identified LAVO with high sensitivity. Addition of the item best gaze to the original FAST score (G-FAST) or high scores on other simplified stroke scales increased specificity. The NIHSS symptom profiles representing total anterior syndromes showed a 10-fold increased likelihood for LAVO compared with a nonspecific clinical profile. If compared with an NIHSS threshold of ≥6, the prehospital stroke scales performed similarly or even better without losing sensitivity. Conclusions—: Simple modification of the face–arm–speech–time score or evaluating the NIHSS symptom profile may help to stratify patients' risk of LAVO and to identify individuals who deserve rapid transfer to comprehensive stroke centers. Prospective validation in the prehospital setting is required. Abstract : Supplemental Digital Content is available in the text.